Pemanfaatan Kebijakan Corporate Social Responsibility Sebagai Upaya Peningkatan Inclusive Business Perbankan Di Indonesia - Hari Sutra Disemadi (Faculty of Law, Andalas University, 2020)
The new paradigm in the banking business is a change in corporate goals from profit-oriented to stakeholder-oriented. Efforts to synergize the matter can bank do Corporate Social Responsibility or CSR. The implementation of CSR by banks is intended to develop the economy in increasing the quality of people's lives and the environment that involves community participation because the community is the party that feels the most impact obtained from the implementation of CSR. The research method used in this study is a normative legal research method with a statutory approach and conceptual approach. This study shows that the legality of implementing CSR for banks is contained in Law Number 25 of 2007 concerning Investment, Law Number 21 of 2008 concerning Sharia Banking and other regulations relating to CSR. The implementation of CSR by banks can benefit the banks themselves. For example, being able to create a